The GH/IGF-1 axis in ageing and longevity - Junnila, Riia K. (2013)
Secretion of growth hormone (GH), and consequently that of insulin-like growth factor 1 (IGF-1), declines over time until only low levels can be detected in individuals aged ≥60 years. This phenomenon, which is known as the ‘somatopause’, has led to recombinant human GH being widely promoted and abused as an antiageing drug, despite lack of evidence of efficacy. By contrast, several mutations that decrease the tone of the GH/IGF-1 axis are associated with extended longevity in mice. In humans, corresponding or similar mutations have been identified, but whether these mutations alter longevity has yet to be established. The powerful effect of reduced GH activity on lifespan extension in mice has generated the hypothesis that pharmaceutically inhibiting, rather than increasing, GH action might delay ageing. Moreover, mice as well as humans with reduced activity of the GH/IGF-1 axis are protected from cancer and diabetes mellitus, two major ageing-related morbidities. Here, we review data on mouse strains with alterations in the GH/IGF-1 axis and their effects on lifespan. The outcome of corresponding or similar mutations in humans is described, as well as the potential mechanisms underlying increased longevity and the therapeutic benefits and risks of medical disruption of the GH/IGF-1 axis in humans.